Vibração de barras em pequena amplitude com efeito geométrico - Wahrhaftig, Alexandre de Macedo; Brasil, Reyolando Manoel Lopes Rebello da Fonseca; Balthazar, José Manoel [UNESP] (My University, 2010)
In engineering a large number of structures may be modeled as cantilevers. Due to their intrinsic characteristics some of these structures are sensitive to actions of a dynamic nature. Gusts of wind are excitations of a dynamic nature upon which the fundamental frequency of vibration is an important factor for the calculation of the structural response. Taking into account the effect of the axial force upon the natural frequencies of a structure usually leads towards systems of differential equations of unviable solution from the engineer’s practical point of view. This article develops a simple mathematical expression for the calculation of the fundamental frequency of balanced structures in small ranges and takes into account the presence of the axial demand. This expression has been validated by dynamic laboratory testing.

Na engenharia, um grande número de estruturas podem ser modeladas como barras em balanço. Algumas dessas estruturas, por características que lhe são intrínsecas, são sensíveis a ações de natureza dinâmica. A frequência fundamental de vibração é fator preponderante para o cálculo das forças devidas ao vento. Normalmente, a consideração do efeito da força axial sobre as frequências naturais de uma estrutura remete a sistemas de equações diferenciais com solução inviável do ponto de vista da vida prática do engenheiro. Este artigo desenvolve uma expressão matemática simples para o cálculo, em pequenas amplitudes, da frequência fundamental para barras em balanço, que leva em conta a presença da solicitação axial. Essa expressão foi validada por ensaios dinâmicos em laboratório.
Vibration of bars in small range including geometric effect
Keywords: Structural dynamics; Geometric non linearity; Virtual works; Experimental investigation; Natural frequencies of vibration; Dinâmica das estruturas; Não-linearidade geométrica; Princípio dos trabalhos virtuais; Investigação experimental; Frequência natural de vibração